2014
DOI: 10.1088/0031-8949/89/7/075103
|View full text |Cite
|
Sign up to set email alerts
|

Delaying disappearance of entanglement by the linear modulation of atom-field coupling

Abstract: By considering a double Jaynes-Cummings (JC) model with linear modulation of the atom-field coupling coefficients, we investigate the entanglement evolution between two atoms, and focuss on the effect of the linear sweep on the entanglement. The results show that the entanglement is very sensitive to the linear modulation of the atom-field coupling coefficients. Both for onephoton processes and for two-photon processes, the disappearance of the initial entanglement is delayed due to the linear modulation as co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Generation and preservation of the quantum entanglement between the qubit and field have played an important role for both fundamental quantum theories and experiments , and they are still a challenge for real applications [38][39][40][41][42][43][44][45][46][47][48], such as quantum key distribution and teleportation. In theory, it is feasible to generate and preserve quantum entanglement based on the well-known Jaynes-Cummings model [49][50][51][52][53][54][55][56]. There have some physical systems dealing with quantum correlation and entanglement through autocorrelation function recently [57][58][59][60], such as semiconductor microcavities [59] and optomechanics [60].…”
Section: Introductionmentioning
confidence: 99%
“…Generation and preservation of the quantum entanglement between the qubit and field have played an important role for both fundamental quantum theories and experiments , and they are still a challenge for real applications [38][39][40][41][42][43][44][45][46][47][48], such as quantum key distribution and teleportation. In theory, it is feasible to generate and preserve quantum entanglement based on the well-known Jaynes-Cummings model [49][50][51][52][53][54][55][56]. There have some physical systems dealing with quantum correlation and entanglement through autocorrelation function recently [57][58][59][60], such as semiconductor microcavities [59] and optomechanics [60].…”
Section: Introductionmentioning
confidence: 99%
“…We showed that the entanglement sudden death can be controlled by these transient e¤ects. Transient e¤ects has also been studied elsewhere [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…situations, these transient effects can be realized by a very slow shift or a sudden jump of the interacting field. The influence of the transient effects on the entanglement was considered elsewhere for different systems[13][14][15].The Hamiltonian of the system becomes ( )…”
mentioning
confidence: 99%